Hyperandrogenism in a postmenopausal woman: a rare case of ectopic adrenal cortical gland. (4th March 2017) - Guarino, Antonella; Di Benedetto, Luisa; Giovanale, Valentina; Rampioni Vinciguerra, Gian Luca; Stoppacciaro, Antonella; Bellati, Filippo; Caserta, Donatella
Abstract: Most frequent causes of androgenic manifestation are Cushing's syndrome, PCO, benign and malignant androgen-secreting non adrenal tumors and iatrogenic hirsutism. Hyperplasia or neoplasms of ectopic adrenocortical gland are rare. We report a case of a 63-year old female with hirsutism and alopecia. Laboratory data highlighted increased levels of androgens. Diagnostic imaging revealed normal morphology of adrenocortical gland and ovaries. In view of the clinical picture and suspected diagnosis of extra-adrenal cause, she underwent bilateral salpingo-oophorectomy. Histologic examination showed an ectopic adrenal gland with adenoma in the ovarian and peri-ovarian tissue. At six months of follow up, the patients has no sign of hyperandrogenism. In case of hyperandrogenism in postmenopausal women and in the absence of the adrenocortical gland abnormality, ovarian origin should be considered in the differential diagnosis.